Development of a revised version of the transdiagnostic skills scale (T2S-R) - Vancappel, Alexis; Gillet, Nicolas; Fouquereau, Evelyne; Chevalier, Séverine; Aubouin-Bonnaventure, Julia; Coillot, Hélène; Mangolini, Anna; Jansen, Eline; Dicosimo, Cinzia; El-Hage, Wissam (Frontiers in Psychology, 2024)
Introduction The transdiagnostic approach has been shown to offer promising prospects in psychopathology, based on the observation that common factors may be involved in different psychiatric disorders. The transdiagnostic skills scale (T2S) was developed recently to assess the skills that are disrupted in these disorders. However, studies have shown that the T2S has lower predictive power for externalizing than internalizing disorders. This may be due to the fact that the skills assessed do not include the control of urges and cravings. The aims of the current study are thus to develop a revised version of the T2S (T2S-R) integrating this dimension, and to assess its factor structure and invariance across employment status (workers vs. students) and the level of psychopathology. Method We recruited 1,298 French participants online through social media. They completed the revised version of the T2S and the symptomatic transdiagnostic test (S2T), which evaluates 11 clusters of psychiatric symptoms. We assessed the factor structure, internal consistency, invariance, and predictive validity of the revised T2S. Results We found a good fit for a bifactor exploratory structural equation modeling (B-ESEM) approach including a global skills factor and seven specific factors. The results also indicate that the new dimension (i.e., control of urges and cravings) has good predictive value, especially for externalizing problems. We also found total invariance of the scale across employment status and partial invariance across the level of psychopathology. Conclusion The revised version of the T2S-R has good psychometric properties. It predicts better externalizing problems than the original version. However, the scale remains more correlated with internalizing than externalizing problems. We discuss the implications of the results on the transdiagnostic conceptualization and the interest of using a mixed approach combining transdiagnostic and diagnostic analyses.